The Impact of Information and Firm Size on Earnings Management in Indonesia’s Primary Consumer Sector Companies - Muliyani, Muliyani; Syamsudin, Syamsudin (Indonesian Financial Review, 2025)
This study examines the influence of information asymmetry and firm size on earnings management in Indonesian listed firms. Using panel data analysis, the research evaluates both individual and joint effects of these variables. Descriptive statistics indicate a moderate level of earnings management, with firms exhibiting both income-increasing and income-decreasing adjustments. The results of hypothesis testing reveal that information asymmetry alone does not significantly affect earnings management (p = 0.1764), while firm size has a significant negative effect (p = 0.0001), suggesting that larger firms engage in less opportunistic reporting. However, the F-test shows that information asymmetry and firm size jointly have a significant impact on earnings management (p = 0.036), explaining 34.72% of the variation in the dependent variable. These findings align with agency theory, which emphasizes managerial discretion under information imbalance, and signaling theory, which highlights the strategic use of earnings to communicate firm performance. The study underscores the importance of governance and monitoring mechanisms in mitigating earnings manipulation in Indonesian firms.